Monotone and oscillatory behavior of certain fourth order nonlinear dynamic equations - Said R. Grace (2018)
Monotone and oscillatory behavior of solutions of the fourth order dynamic equation (a(xΔΔ)α) ΔΔ(t)+(t)(xσ)β(t) = 0 with the property that x(t)/∫tt0 ∫ at0a-1/a(τ)ΔτΔs → as t → ∞ are established. © Dynamic Publishers, Inc.